Midterm result of custom-made iliac branch device for common iliac aneurysm with and without abdominal aortic aneurysm. (21st December 2020) - Huang, Chun-Yang; Chen, Po-Lin; Lu, Hsin-Ying; Hsu, Hung-Lung; Kuo, Tzu-Ting; Chen, I.-Ming; Hsu, Chiao-Po; Shih, Chun-Che
Abstract: OBJECTIVES: Although commercial iliac branch devices offer a new and valid endovascular approach to treating iliac aneurysm and effectively preserve antegrade flow of the internal iliac artery, their use may not be suited for all types of challenging anatomy, especially isolated common iliac artery aneurysm. Our custom-made iliac bifurcation device has a unique design and excludes both combined and isolated iliac branch aneurysm. This study validated the efficacy and safety of the custom device by comparing clinical outcomes between groups receiving commercial and custom devices. METHODS: Data of consecutive patients receiving iliac bifurcation device implantation for iliac aneurysm with or without concomitant endovascular repair for abdominal aortic aneurysm from January 2010 to May 2019 were reviewed. RESULTS: Iliac bifurcation device implantation with or without concomitant abdominal aortic aneurysm stent grafting was completed in 46 patients (commercial, n  = 35; custom, n  = 11). No significant differences were observed regarding postoperative complications, occlusion or endoleak. Comparisons of primary (80.8% vs 85.7%, P  = 0.88) and secondary (86.5% vs 85.7%, P  = 0.85) patency and freedom from reintervention (88.2% vs 100%, P  = 0.33), all-cause mortality (78.6% vs 100%, P  = 0.25) and aneurysm-related mortality (100% vs 100%, P  = 1.00) also indicated no differences at a 5-year surveillance point. Furthermore, the iliac aneurysms of the groups displayed similar shrinkage 1 year after procedures. CONCLUSIONS: For iliac aneurysm, the novel custom-made iliac bifurcation device is an adaptable design not inferior to commercial devices with regard to postoperative complications, bridge occlusion, endoleak and short-term aneurysm remodelling. It provides an alternative for treatment, particularly when certain anatomic challenges are present. Clinical trial registration: 2018-07-050BC, 2017-01-023ACF.